The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.13102/rscdauefs.v9i0.3739
|View full text |Cite
|
Sign up to set email alerts
|

Importância do apoio familiar no período gravídico-gestacional sob a perspectiva de gestantes inseridas no PHPN

Abstract: O presente estudo tem por objetivo analisar a percepção de gestantes sobre a importância do apoio familiar no período gravídico-gestacional, tendo como referência as vivências daquelas cadastradas no Sistema de Informação do Pré Natal (SISPRENATAL). Trata-se de estudo observacional, descritivo, de corte transversal quantiqualitativo, com dados coletados em entrevistas domiciliares realizadas junto a 80 gestantes inseridas no Programa de Humanização no Pré Natal e Nascimento (PHPN) a partir de 2016, na … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
14

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 11 publications
0
2
0
14
Order By: Relevance
“…Similarly, a study reveals that the fact that women are accompanied by their husband or partner seems to have a positive influence on the duration of breastfeeding. 16 On the other hand, although the spouse is pointed out as the greatest source of support in our study, authors identified that, when breast intercurrences occur, they do not offer this support, 17 because they did not receive orientation during prenatal care on this topic, which would help them understand the situation and the difficulties of this process. 15 Thus, it is essential that prenatal care be centered on the family, that the person considered most important to the woman be identified and participate in all events held in this scenario.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Similarly, a study reveals that the fact that women are accompanied by their husband or partner seems to have a positive influence on the duration of breastfeeding. 16 On the other hand, although the spouse is pointed out as the greatest source of support in our study, authors identified that, when breast intercurrences occur, they do not offer this support, 17 because they did not receive orientation during prenatal care on this topic, which would help them understand the situation and the difficulties of this process. 15 Thus, it is essential that prenatal care be centered on the family, that the person considered most important to the woman be identified and participate in all events held in this scenario.…”
Section: Discussionmentioning
confidence: 72%
“…Research conducted with the purpose of identifying pregnant women's perception of the family support received during the pregnancy and puerperal period showed that most of the women interviewed had a positive perception of the support received and valued family involvement during this period, which positively influences the prenatal, childbirth, and puerperal periods, including breastfeeding. 16 By relating to their social network during breastfeeding, nurturers expect to receive understanding and support and point to the intention of maintaining these relationships with a positive aspect in order to overcome difficulties and achieve success in breastfeeding. 20 A positive relationship with a person considered a source of primary support can positively influence the initiation and maintenance of BF.…”
Section: Discussionmentioning
confidence: 99%
“…O apoio familiar e de amigos também foi mencionado como peça importante na organização da linha de defesa das mulheres e agrega um papel fundamental para que todo o percurso gestacional ocorra com naturalidade e tranquilidade. Carinho e conduta positiva advindas de amigos, colegas de trabalho, vizinhos e familiares contribuem de maneira positiva e significativa no desenvolvimento saudável da gestação (18) .…”
Section: Discussionunclassified
“…Vivenciar a reaproximação familiar, conquistada com a chegada de um bebê com malformação, foi apontado como sinônimo de união e alegria, con-tribuindo para o fortalecimento da linha de resistência. A vivência de uma gravidez, mesmo que difícil e conflituosa, ultrapassa limites, promove mudanças nas pessoas como irmãos, pais, familiares, que passam por alterações de exigências internas e influenciadas pelo meio vivido, capazes de transformar adversidades em esquecimentos (14,(17)(18) .…”
Section: Discussionunclassified
“…19 Receber apoio, afeto, cuidado e proteção na gestação é fundamental para que o período gravídico puerperal transcorra com tranquilidade. 20 É importante destacar que, quanto antes a DPP for identificada, maiores as chances de prevenir os danos, 16 como a diminuição do vínculo mãe-bebê e os atrasos no desenvolvimento social e cognitivo dos filhos. 6 Dessa maneira, os profissionais de saúde podem avaliar o risco entre as puérperas e prestar os cuidados adequados para evitar que a depressão se desenvolva ou, no caso de já instalada, não se agrave.…”
Section: Introductionunclassified